Detection of Genomic Structural Variants from Next-Generation Sequencing Data - Tattini, Lorenzo; D’Aurizio, Romina; Magi, Alberto (Frontiers in Bioengineering and Biotechnology, 2015)
Structural variants are genomic rearrangements larger than 50 bp accounting for around 1% of the variation among human genomes. They impact on phenotypic diversity and play a role in various diseases including neurological/neurocognitive disorders and cancer development and progression. Dissecting structural variants from next- generation sequencing data presents several challenges and a number of approaches have been proposed in the literature. In this mini review we describe and summarise the latest tools – and their underlying algorithms – designed for the analysis of whole-genome sequencing, whole-exome sequencing, custom captures and amplicon sequencing data, pointing out the major advantages/drawbacks. We also report a summary of the most recent applications of third-generation sequencing platforms. This assessment provides a guided indication – with particular emphasis on human genetics and copy number variants – for researchers involved in the investigation of these genomic events.